Characterization of race 65 of Colletotrichum lindemuthianum by sequencing ITS regions - Marcela Coelho; Maria Celeste Gonçalves-Vidigal; Lorenna Lopes de Sousa; Maria Paula Barion Alves Nunes; Rafhael Felipin Azevedo; Marta Zulema Galván (Acta Scientiarum. Agronomy, 2016)
The present work aimed characterize isolates of C. lindemuthianum race 65 from different regions in Brazil by ITS sequencing. A total of 17 isolates of race 65, collected in the states of Mato Grosso, Minas Gerais, Paraná, Santa Catarina and São Paulo, were studied. Analysis of the sequences of isolates 8, 9, 12, 14 and 15 revealed the presence of two single nucleotide polymorphisms (SNPs) in the ITS1 region at the same positions. These isolates, when analyzed together with the sequence of isolate 17, revealed a SNP in the ITS2 region. The highest genetic dissimilarity, observed between isolates 11 and  3 and between isolates 11 and 10, was 0.772. In turn, isolates 7 and 2 were the most similar, with a value of 0.002 for genetic distance. The phylogenetic tree obtained based on the sequences of the ITS1 and ITS2 regions revealed the formation of two groups, one with a subgroup. The results reveal high molecular variability among isolates of race 65 of C. lindemuthianum.